Ciptakan Sekolah Aman: Psikoedukasi Cegah Bullying bagi Siswa Sekolah Dasar - Puspita Puji Rahayu (Jurnal Ragam Pengabdian, 2025)
Bullying in elementary schools, whether in the form of verbal or physical violence, is a serious problem that can disrupt socio-emotional development, lower academic achievement, and pose long-term psychological risks for children. This phenomenon remains prevalent in Indonesia, thus requiring early prevention efforts that are structured and involve all school stakeholders. This community service activity aimed to provide psychoeducation to elementary school students to enhance their awareness, empathy, and social skills in preventing and addressing bullying. The program was conducted at SD Negeri Karanganyar Gunung 02, Semarang City, involving 120 students from grades I to VI. The implementation methods included interactive material delivery, group discussions, role-play activities, and the formulation of a joint “Safe School” commitment involving students, teachers, and parent representatives. The materials were presented in simple language and incorporated engaging activities to facilitate students’ understanding.The results indicated an improvement in students’ understanding, as reflected in their ability to identify various forms of bullying, explain its impacts, and describe appropriate actions when becoming a victim or witness. In addition, teachers reported an increase in mutual respect among students and a decrease in the frequency of minor aggressive behaviors in the classroom within two weeks after the program. This initiative proved effective in creating a safer and more positive school climate and is recommended for integration into elementary school character-building programs.